PRODUCTIVE LEARNINGIS CONSIDEREDAS ACHANGE STIMULUS IN MAINSTREAMSCHOOLS OFPEDAGOGICAL SYSTEM - Targamadzė, Vilija (Acta Paedagogica Vilnensia, 2011)
The aim of the research is to unfold productive learning as a possible change stimulus in mainstream schools of education system. It is the conception, origin and dispersion of productive learning in the context of education which is disputed. In fact, productive learning is revealed as a certain pedagogical system with its own metodological access. L. Vygotskis cultural-historical conception is provided based on two aspects which reveal development zone and the closest development zone. It is related to productive learning. The content, structural, organizational distinctions of productive studying is being under investigation unfolding its relation with the traditional mainstream school. As a matter of fact, productive learning is revealed as a certain pedagogical system, however, the same standards are its objective. In addition to that, productive learning is discussed over in Lithuanian education context demonstrating its relation with the traditional mainstream school. Attention is concentrated on the aspects that productive learning belongs to the paradigm of liberal education, it discords with academic teaching prevailing in Lithuania and/or teaching traditions inspiring to project another education system in the mainstream sphere. Furthermore, necessary presumptions for productive learning projection and implementation are metodological (giving sense to the concept of productive learning and following the modeling of pedagogical system), law, human resources, etc.
Keywords: roductive learning; historical source of productive learning; spread; mainstream school; L. Vygotskis cultural-historical conception; model of productive learning; presumptions of implementation